Paz Marquez Benitez one woman's life, letters, and writing - Licuanan, Virginia Benitez (Quezon City Ateneo de Manila University Press, 1995)
"This book on the life, letters, and writings of Paz Marquez Benitez (1894-1983) marks the birth centenary of this extraordinary woman. Paz Marquez Benitez was among the first generation of Filipinos educated under the Americans. She became a professor of English, as well as the country's first and foremost short story writer in English. The course in short story writing that she taught at the University of the Philippines for thirty years has been credited with having produced some of the brightest and best Filipino writers in English. She also was the founders of the first American-style college for women in the Philippines (the Philippines Women's College). She founded and edited the first Filipino women's magazine. With her husband Dean Francisco Benitez - the founder and first dean of the College of Education of the University of the Philippines - she started the country's first professional magazine for teachers, the Philippine Journal of Education. After her husband died in 1951, she took over as its editor until her death at the age of eighty-nine."--Back cover.
Part I. The years of youth, 1894-1929 -- Transition and transformation -- Memories of many childhoods -- Part II. The golden years, 1930-1939 -- The high tide of life -- Letters to a daughter in America -- Memories in photographs -- Letters to a husband of twenty-five years -- Part III. The years of change, 1940-1983 -- War and aftermath -- Growing old is growing up -- The "real" Paz Marquez Benitez -- After all is said and done -- Afterword -- Index of personal names.
FI-6991g donated by Dr. Damiana L. Eugenio.
Keywords: Benitez, Paz Marquez -- 1894-1983 -- Correspondence; Women authors, Philippine -- Biography; Women educators -- Biography. -- Philippines